On Simple Ruin Expressions in Dependent Sparre Andersen Risk Models. (March 2014) - Albrecher, Hansjörg; Boxma, Onno J.; Ivanovs, Jevgenijs
Abstract : In this note we provide a simple alternative probabilistic derivation of an explicit formula of Kwan and Yang (2007) for the probability of ruin in a risk model with a certain dependence between general claim interoccurrence times and subsequent claim sizes of conditionally exponential type. The approach puts the type of formula in a general context, illustrating the potential for similar simple ruin probability expressions in more general risk models with dependence.